OLD SLAVIC SYMBOLS IN THE G.S. SKOVORODA’S PHYLOSOPHY - Михалевич, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problem of the old slavic symbols in G.S. Skovoroda’s phylosophy is considered. The author analуses the matter of the OLD SLAVIC symbols, their gradual christianization and following rationalization in phylosophy.